Binding of Gd3+ to the neuronal signalling protein calexcitin identifies an exchangeable Ca2+‐binding site. Issue 4 (1st April 2016) - Chataigner, Lucas; Guo, Jingxu; Erskine, Peter T.; Coker, Alun R.; Wood, Steve P.; Gombos, Zoltan; Cooper, Jonathan B.
Abstract : Calexcitin is a two‐domain, neuron‐specific signalling protein which possesses four EF‐hand motifs, of which only the first three are functional metal‐binding sites. Recombinant calexcitin from L. pealei has been crystallized with an equimolar concentration of Gd 3+ in the presence of trace Ca 2+, and it was demonstrated that it is the Ca 2+ ion bound to the N‐terminal EF‐hand which becomes replaced by the exogenous heavy‐metal ions. Abstract : Calexcitin was first identified in the marine snail Hermissenda crassicornis as a neuronal‐specific protein that becomes upregulated and phosphorylated in associative learning. Calexcitin possesses four EF‐hand motifs, but only the first three (EF‐1 to EF‐3) are involved in binding metal ions. Past work has indicated that under physiological conditions EF‐1 and EF‐2 bind Mg 2+ and Ca 2+, while EF‐3 is likely to bind only Ca 2+ . The fourth EF‐hand is nonfunctional owing to a lack of key metal‐binding residues. The aim of this study was to use a crystallographic approach to determine which of the three metal‐binding sites of calexcitin is most readily replaced by exogenous metal ions, potentially shedding light on which of the EF‐hands play a `sensory' role in neuronal calcium signalling. By co‐crystallizing recombinant calexcitin with equimolar Gd 3+ in the presence of trace Ca 2+, EF‐1 was shown to become fully occupied by Gd 3+ ions, while the other two sites remain fully occupied by Ca 2+ . The structure of the Gd 3+ –calexcitin complex has been refined to an R factor of 21.5% and an R free of 30.4% at 2.2 Å resolution. These findings suggest that EF‐1 of calexcitin is the Ca 2+ ‐binding site with the lowest selectivity for Ca 2+, and the implications of this finding for calcium sensing in neuronal signalling pathways are discussed.